Cannabis use correlates with aggressive behavior and long-acting injectable antipsychotic treatment in Asian patients with schizophrenia. (18th August 2019) - Park, Seon-Cheol; Oh, Hong Seok; Tripathi, Adarsh; Kallivayalil, Roy Abraham; Avasthi, Ajit; Grover, Sandeep; Tanra, Andi Jayalangkara; Kanba, Shigenobu; Kato, Takahiro A.; Inada, Toshiya; Chee, Kok Yoon; Chong, Mian-Yoon; et al.
Abstract: Background: Although cannabis use has been linked with schizophrenia in a dose–response pattern, to our knowledge, the relationship between cannabis and schizophrenia has rarely been reported in Asian population. Aim: We compared the clinical characteristics and psychotropic prescription patterns between cannabis users and non-users among Asian patients with schizophrenia. Moreover, we aimed to identify the independent correlates of cannabis use in these subjects. Methods: We performed the analysis of the data from the Research on Asian Psychotropic Prescription Patterns for Antipsychotics (REAP-AP), a collaborative consortium survey used to collate the prescription patterns for antipsychotic and other psychotropic medications in patients with schizophrenia in Asia. We included 132 schizophrenia patients in the group of lifetime cannabis use and 1756 in the group that had never used cannabis. A binary logistic model was fitted to detect the clinical correlates of lifetime cannabis use. Results: Adjusting for the effects of age, sex, geographical region, income group, duration of untreated psychosis, and Charlson comordity index level, a binary logistic regression model revealed that lifetime cannabis use was independently associated with aggressive behavior [adjusted odds ratio (aOR) = 1.582, 95% confidence interval (CI) = 1.006–2.490, p  = .047] and with long-acting injectable antipsychotic treatment (aOR = 1.796, 95% CI = 1.444–2.820, p  = .001). Conclusion: Our findings indicate a close link between lifetime cannabis use and aggressive behavior. The use of long-acting, injectable antipsychotics preferentially treats the aggressive behavior cannabis users among patients with schizophrenia in Asia, especially, the South or Southeast Asia.